Pelatihan Aplikasi SPSS untuk Pemecahan Masalah Perhitungan pada Statistika Deskriptif di SMA Negeri 1 Maluku Tengah - Muhammad Yahya Matdoan; Muhidin Jariyah; Irfandy Walli (LPPM Universitas Flores, 2021)
Statistics is a very difficult material, especially in the process of calculating and analyzing data which tends to be complicated because it requires accuracy and accuracy in its calculations. However, along with the rapid advancement in technology, various computer applications that are specifically designed to help calculate statistical data have emerged, one of which is SPSS. The method of activities held in community service (PKM) is in the form of SPSS training. Participants in this activity were students of SMA Negeri 1 Maluku Tengah. The conclusion obtained in this service is the results of the evaluation given at the end of the activity, of the 28 training participants, all students who took part in the training were able to complete the assigned tasks very well. In addition, teachers must equip students with programming skills, especially statistical and mathematical applications, so that they can arouse students' enthusiasm and interest in learning mathematics and statistics. The necessary follow-up is that it is necessary to carry out further training to hone the interests and abilities of teachers more deeply.